1986
DOI: 10.1111/j.1365-2621.1986.tb13887.x
|View full text |Cite
|
Sign up to set email alerts
|

Antinutritional factors in Moth Bean (Vigna aconitifolia): Varietal Differences and Effects of Methods of Domestic Processing and Cooking

Abstract: Significant varietal differences were observed in the contents of phytic acid, saponin and trypsin inhibitor activity of four varieties of Moth bean (Vigna aconitifolia Jacq.). Tannins and lectins were absent. The dry seeds were given different treatments including soaking, sprouting and cooking and the changes in the level of the antinutritional factors were estimated. Soaking the seeds in plain water and mineral salt solution for 12 hr decreased phytic acid to the maximum (46-50%) whereas sprouting for 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
72
3
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(94 citation statements)
references
References 31 publications
12
72
3
5
Order By: Relevance
“…trogênio fecal em animais (COSTA DE OLIVEIRA et al, 2001). Os taninos também afetam a digestibilidade de carboidratos e a biodisponibilidade de minerais (KHOKHAR; CHAUHAN, 1986;COELHO;LAJOLO, 1993;CARBONARO et al, 1996).…”
Section: Taninosunclassified
See 3 more Smart Citations
“…trogênio fecal em animais (COSTA DE OLIVEIRA et al, 2001). Os taninos também afetam a digestibilidade de carboidratos e a biodisponibilidade de minerais (KHOKHAR; CHAUHAN, 1986;COELHO;LAJOLO, 1993;CARBONARO et al, 1996).…”
Section: Taninosunclassified
“…A diminuição observada no conteúdo de fitatos durante a maceração pode ser atribuída a uma lixiviação dos íons fitatos na água sob a influência de um gradiente de concentração que provoca a difusão deste nutriente para a água de maceração (KHOKHAR; CHAUHAN, 1986;COSTA DE OLIVEIRA et al, 2001). Porém estas perdas também podem ser devido a mudanças na permeabilidade da membrana externa dos grãos (KHOKHAR; CHAUHAN, 1986).…”
Section: Fitatosunclassified
See 2 more Smart Citations
“…Cooking of soaked dry bean seeds at atmospheric pressure caused more reductions in antinutrients contents than pressure cooking (Nergiz and Gökgöz, 2007). It was reported that pressure cooking had the most pronounced effect in improving the in vitro protein digestibility of presoaked moth bean seeds compared to ordinary cooking, soaking or sprouting (Khokhar and Chanhan, 1986). Rao (1974) has reported a reduction in the available lysine of chickpea by increasing the time and temperature of processing.…”
Section: Introductionmentioning
confidence: 99%